Dysfunction in the fellow eyes of strabismic and anisometropic amblyopic children assessed by visually evoked potentials - Andrade,Eric Pinheiro (2016)
ABSTRACT Purpose: To evaluate visual acuity and transient pattern reversal (PR) visual evoked potentials (VEPs) in the fellow eyes of children with strabismic and/or anisometropic amblyopia. Methods: Children diagnosed with strabismic and/or anisometropic amblyopia were recruited for electrophysiological assessment by VEPs. Monocular grating and optotype acuity were measured using sweep-VEPs and an Early Treatment Diabetic Retinopathy Study chart, respectively. During the same visit, transient PR-VEPs of each eye were recorded using stimuli subtending with a visual angle of 60', 15', and 7.5'. Parameters of amplitude (in μV) and latency (in ms) were determined from VEP recordings. Results: A group of 40 strabismic and/or anisometropic amblyopic children (22 females: 55%, mean age= 8.7 ± 2.2 years, median= 8 years) was examined. A control group of 19 healthy children (13 females: 68.4%, mean age= 8.2 ± 2.6 years, median= 8 years) was also included. The fellow eyes of all amblyopes had significantly worse optotype acuity (p=0.021) than the control group, regardless of whether they were strabismic (p=0.040) or anisometropic (p=0.048). Overall, grating acuity was significantly worse in the fellow eyes of amblyopes (p=0.016) than in healthy controls. Statistically prolonged latency for visual angles of 15' and 7.5' (p=0.018 and 0.002, respectively) was found in the strabismic group when compared with the control group. For the smaller visual stimulus (7.5'), statistically prolonged latency was found among all fellow eyes of amblyopic children (p<0.001). Conclusions: The fellow eyes of amblyopic children showed worse optotype and grating acuity, with subtle abnormalities in the PR-VEP detected as prolonged latencies for smaller size stimuli when compared with eyes of healthy children. These findings show the deleterious effects of amblyopia in several distinct visual functions, mainly those related to spatial vision.